Involvement of women in income generating activities: changes over time - Banu, Dilruba (BRAC, 2019)
This paper explores the changes in the involvement of women in income generating activities with their participation in BRAC programmes over time. It is based on a timeseries data collected from the same households with three years of interval. Participation in BRAC progranunes created an opportunity for women to he involved in cash earning although it did not increase with length of membership. Women's involvement in cash earning was more common in female headed and low income households. Intensity, inputs, time spent, size and market facilities regulated the income from IGA as wen. With improvement in the economic condition of member households the involvement in income generating activities has been decreased. Mainly women who were involved in selfemployed activities continued their work.